Penentuan Faktor Kadar Caj Perkhidmatan Bangunan Kediaman Berstrata - Nurin Izazi Haziyah Hizam; Kasim, Rozilah (Research in Management of Technology and Business, 2024)
The issue of non-uniformity of service charges has created problems for residents of stratified residential buildings. This is because the service charged for each strata residential building unit is different. The matter needs to be standardised by determining a service charge guide for each stratified residential unit considering all service charge determination factors. This study focuses on identifying the factors and determining the ’ranking’ factors that affect stratified residential building services. The research methodology used is a quantitative method with survey questionnaire forms distributed to the respondents of strata management bodies in Johor Bahru. The descriptive and frequency analyses were performed using SPSS software. The study’s results identify the factors and determine the ’ranking’ factor that affects the service charge rate of the strata residential buildings. The findings are useful as a guide to the management body, especially in determining service charges for stratified residential buildings.